ChemInform Abstract: A Modular, Air‐Stable Nickel Precatalyst. Issue 36 (September 2015) - Shields, Jason D.; Gray, Erin E.; Doyle, Abigail G.
Abstract The synthesis of an air‐stable nickel precatalyst is developed and the utility of the complex as catalyst is demonstrated for a range of Ni‐catalyzed coupling reactions.